How Do Learning Organization Drive Innovation in Hospitals? The Mediating Role of Employee Resilience and Work Engagement under High Job Demands - Windi Retno Dwi Mulia; Fatmah Bagis; Suyoto Suyoto; Arini Hidayah; Ahmad Haruna Abubakar (CV. Creative Tugu Pena, 2026)
This study examines the effect of a learning organization on hospital innovation, with employee resilience and work engagement serving as potential mediating variables. The conceptual framework is grounded in Organizational Learning Theory and the Job Demands–Resources (JD-R) Theory. Employing a quantitative approach, this study replicates and extends the model proposed by Mohammad et al. (2024) within the healthcare context. The study population comprised 966 employees from three hospitals in Banjarnegara Regency, Indonesia. A sample of 342 respondents was selected using stratified random sampling.. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that a learning organization significantly influences innovation and employee resilience, but not significantly on work engagement. Furthermore, employee resilience has a positive and significant effect on innovation and mediates the relationship between a learning organization and innovation. Conversely, work engagement has no significant effect on innovation and does not act as a mediator. These findings suggest that in a hospital context with high work demands and a procedural work structure, employee psychological resilience is a more important determinant of innovation than job engagement. Theoretically, this study enriches Organizational Learning Theory and JD-R Theory by confirming that under conditions of high job demands, innovation is driven more by psychological resilience than job engagement.